2012
DOI: 10.1002/chem.201103628
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of the 4,5‐Didehydroisoquinolinium Cation

Abstract: The chemical properties of a 1,8-didehydronaphthalene derivative, the 4,5-didehydroisoquinolinium cation, were examined in the gas phase in a dual-cell Fourier-transform ion cyclotron resonance (FT-ICR) mass spectrometer. This is an interesting biradical because it has two radical sites in close proximity, yet their coupling is very weak. In fact, the biradical is calculated to have approximately degenerate singlet and triplet states. This biradical was found to exclusively undergo radical reactions, as oppose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 42 publications
(46 reference statements)
2
26
0
Order By: Relevance
“…253 72 (S-T splitting = −0.6 kcal/mol) is a positively charged analog of 1,8-didehydronapthalene, which has shown interesting chemical properties 254257 attributed to its nearly degenerate singlet and triplet states (S-T splitting = −0.9 kcal/mol). 258 Examination of the gas-phase reactions of 72 suggested that they mostly occur via radical mechanisms, as opposed to the meta -benzyne analogs discussed above.…”
Section: Properties and Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…253 72 (S-T splitting = −0.6 kcal/mol) is a positively charged analog of 1,8-didehydronapthalene, which has shown interesting chemical properties 254257 attributed to its nearly degenerate singlet and triplet states (S-T splitting = −0.9 kcal/mol). 258 Examination of the gas-phase reactions of 72 suggested that they mostly occur via radical mechanisms, as opposed to the meta -benzyne analogs discussed above.…”
Section: Properties and Reactivitymentioning
confidence: 99%
“…Hence, the C4 radical site was experimentally proven to abstract the first hydrogen atom from cyclohexane, followed by the C5 radical site. 253 Analogous to the reactions with tetrahydrofuran and cyclohexane, the reactions of 72 with dimethyl disulfide and allyl iodide are likely to be initiated by atom or group abstraction by the C4 radical site.…”
Section: Properties and Reactivitymentioning
confidence: 99%
“…These results are in agreement with previouss tudies on relatedb iradicals. [3,4,6,21] However,c ompound 4 is less reactivet han monoradicals 1 and 3 toward almost all of the reagents studied. Only the least reactive monoradical 2 shows similar reaction efficiencies to that of 4.T he low reactivity of singlet (ground state) biradicals has been noted previously, [4-6, 23, 25] and is typically due to stabilizing interactions (i.e.,c oupling) between the two nonbonding electrons.…”
Section: Resultsmentioning
confidence: 87%
“…Previouss tudies have revealed that the C4 radical site is more reactive than that of C5 in biradical 5 due to its greater EA. [21] To identify which radicals itei nt riradical 7 reacts first, the first hydrogen atom abstraction product of 7 (formed upon reaction with cyclohexane) was isolateda nd allowed to react with cyclohexane( Scheme2). The measured reaction efficiency is 3%,w hichi sc omparable to that for the reaction of biradical 4 with cyclohexane (2 %), and quite different from that of 5 (18 %) or 6 (0.002 %a sd etermined in al inear quadrupole ion trap mass spectrometer [28] ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation